Stability in Pelvic Triple Osteotomies in Children Using Resorbable PLGA Screws for Fixation. Issue 9 (October 2021) - Hedelin, Henrik; Larnert, Per; Antonsson, Pavel; Lagerstrand, Kerstin; Brisby, Helena; Hebelka, Hanna; Laine, Tero
Abstract : Background: The triple pelvic osteotomy (TPO) is a major redirectional osteotomy used to improve the acetabular coverage of the femoral head in selected pediatric patients with hip disorders. Traditionally the iliac osteotomy is stabilized by metal screws that require a second surgery for removal. Despite favorable results for both adults and children in related pelvic osteotomies, resorbable implants have not previously been used for TPOs. This study aims to suggest a novel modified TPO surgical method in children using resorbable poly lactic-co-glycolic acid (PLGA) screws for fixation and to radiographically evaluate the postoperative stability achieved by these implants in a case series. Methods: All patients (n=11) with dysplasia of the hip (2), Perthe disease (5), or Down syndrome (4), who underwent primary TPO surgery during 2013 to 2019, using resorbable PLGA screws for fixation were included. The stability of the osteotomy was evaluated in the postoperative radiograph series using the acetabular index, migration percentage, Sharp's angle and the center-edge angle. The osteotomy angle was introduced as a parameter to confirm the postoperative integrity of the achieved correction. All cases were evaluated until radiographic healing of the iliac osteotomy. Hospital notes were analyzed for complications or local reactions in relation to the implants. Results: In all studied hips, the overall achieved correction was well maintained. The mean (SD) correction achieved, from the preoperative images to the last measurable postoperative image, was a 16.7 degrees decrease for Sharp angle, a 20.9 degrees decrease in acetabular index and a 24.7 degrees increase for the center-edge angle, respectively. There were no complications related to the bioabsorption of the implants. Conclusion: The present findings suggest that the modified TPO method, using resorbable PLGA screws, provides sufficient stability and appears to be a promising alternative to traditional TPO. Avoiding implant removal is a major benefit in a pediatric population. Resorbable screws enable the surgeon to place implants with more degrees of freedom since later implant removal is not a limiting factor. Level of Evidence: Level IV—case series. Abstract : Supplemental Digital Content is available in the text.